Liquid Fear: Bauman’s Metaphorical Insights in Relation to Covid-19 Fear Metaphors - Izabela Dixon (Research in Language)
In this study I attempt to demonstrate how Zygmunt Bauman’s insights published in his book entitled Liquid Fear (2006) benefit the cognitive study of the emotion of fear by drawing correspondences between Bauman’s liquid reality and the Covid-19 pandemic. Based on my, largely unpublished, linguistic study of fear and on metaphors pervading Bauman’s work, I extrapolated key components of the fear frame. Having also conducted the study of concepts that dominated the Covid-19 media narratives, I relate and analyse the validity and transferability of conceptual domains within selected contextual models of social and verbal behaviours related to fear. Bauman’s metaphorical observations are woven into the analytical patchwork of this paper.